(untitled) (Research, Society and Development, 2023)
Temporomandibular disorder (TMD) is a collective term that encompasses a group of alterations that affect the temporomandibular joint (TMJ), masticatory muscles and associated structures. This research, carried out between January and July 2022, carried out an integrative review aiming to synthesize the main findings regarding the assistance provided to individuals with TMD, within the scope of Brazilian Primary Care. Methodology: A search was carried out in the databases IBECS, LILACS, MEDLINE, SciELO and Google Scholar. Results: It was observed that, despite this environment being the gateway to the health care of the population, there is a scarcity of studies on the subject, which has important public health relevance, due to the damage (psychological, functional and social) related. Therefore, pertinent information on TMD and the possibilities of clinical management in primary care are presented, which should include adequate identification of the problem, screening, diagnosis and treatment that, in principle, should be conservative and carried out by an interdisciplinary team. In the initial approach, strategies such as welcoming and qualified listening can be used, while therapy can include health education interventions, self-care techniques, physiotherapy, behavioral therapies, and drug use, Integrative and Complementary Practices. Final considerations: This study draws attention to the need for this topic to be more addressed in the scientific community, considering that there is possibly a repressed demand of individuals in need of care, but that it is being inadequately conducted in health units that must be resolving, guarantee the access, longitudinally, comprehensiveness and coordination of care.